Pengaruh Waktu Degradasi Terhadap Fotodegradasi Zat Warna Fenol Red Menggunakan Katalis TiO2-Ag - Sari, Desy Nurhasanah; Ansyarif, Azmalaeni Rifkah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
Photodegradation is one method that can be used to process dye waste. This research aims to examine the effect of radiation time on the photodegradation of phenol red dye using a TiO2-Ag catalyst. This research was carried out using varying radiation times of 5, 10, 20, 30, 45, 60, 85, 90, 120, 150, and 210 minutes. The results showed that the radiation time affected the rate of photodegradation of phenol red dye. The photodegradation rate increases with increasing irradiation time. At 85 minutes of radiation time, the photodegradation rate of phenol red dye reached 82.47%. Based on the results of this research, it can be concluded that the TiO2-Ag catalyst is effective in the photodegradation process of phenol red dye with an optimum radiation time of 85 minutes. The TiO2-Ag catalyst is an effective catalyst in the dye photodegradation process